La interculturalidad con enfoque lingüístico en el proceso de enseñanza y aprendizaje en el colegio técnico agropecuario bilingüe “Jatun Juigua” comunidad Yacubamba, parroquia, matriz cantón Pujilí, provincia Cotopaxi, periodo 2014-2015. Programa de capacitación. - Tipantuña Vega, María Elena (2016)
This research focuses on the development of intercultural student school at “Khatun Juigua". Being the main objective to give to the educational community a detailed analysis of multiculturalism and its impact on the teaching-learning process. It made a field research, bibliography-documented, exploratory and descriptive, it knew through surveys performed for teachers, students and parents, concluding that the cultural degradation involved the teaching process. Furthermore, this research is to guide the decisions that the teacher should take into account the time to teach, with the handing over of a workshop training proposal for educators, parents and students. It considers that the investigated problem it becomes a strength for the preservation of cultural identity in the community, and thus develop awareness among students and teachers on the practice of values intercultural which is not final and who have an approach to this research work, know how to give their contribution to it. To achieve the above described it-collected information to the all institution. It is important to mention that the primary data were collected directly into the place through questionnaires to students, teachers and parents for which it carried out a series of surveys.